Elucidation of reactive oxygen species scavenging pathways of norbergenin utilizing DFT approaches. Issue 12 (21st December 2022) - Haq, Kautsar Ul; Rusdipoetra, Rahmanto Aryabraga; Siswanto, Imam; Suwito, Hery
Abstract : Bergenin is a polyphenolic compound that contains isocoumarin skeletal derived from C -glycosylated 4- O -methylgallic acid. The biological activities of this compound and its derivatives are quite diverse. Recent studies reveal neuroprotective effects in vitro and in vivo in Alzheimer's. Norbergenin is a demethylated form of bergenin, known for better antioxidant capacity and associated with neuroprotective properties through oxidative stress inhibition. This study focused on investigating the scavenging mechanism of norbergenin with the OH, OOH, and O 2 ∙ − as a radical model under physiological and lipid environments. The thermodynamic and kinetic parameters of the hydrogen transfer (HT), single electron transfer (SET), sequential proton lost-electron transfer (SPLET) and radical adduct formation (RAF) mechanisms were determined theoretically by the density functional theory (DFT) at M06-2X/6-311 + + G(d, p) level of theory. Based on the computational results, this compound has proved as an excellent OOH and OH scavenger under physiological conditions better than Trolox and vitamin C, whereas its radical demonstrated as an efficient O 2 ∙ − scavenger.